Unraveling The Complexity of Urban Vulnerability: Challenges And Strategies In Addressing Social Urban Problem In South Sulawesi - Yani, Andi Ahmad; Hans, Amril; Dewi, Dwiana Fajrinawati; Kasogi, Muhammad Adnan; Nugraha, Rahmat Nurul; Yahya, Andi Fitriyani (Pusat Penelitian Kebijakan Pembangunan, Universitas Hasanuddin, 2023)
Street children, homeless individuals, and beggars are intricate societal issues that predominantly manifest in urban regions, especially the urban areas of South Sulawesi. The South Sulawesi Provincial Government and the district/city governments in urban areas have implemented policies to address the issue of street children, homeless individuals, and beggars. However, these policies have not been effectively implemented and have not had a significant impact on addressing the problem in urban areas of South Sulawesi. The provincial and district/city administrations in South Sulawesi have four problems in addressing this social issue: family dysfunction, program limits, community involvement, and limited institutional capability. In South Sulawesi, the provincial and district/city administrations in metropolitan areas oversee inter-regional coordination plans and implement preventive, curative, and rehabilitative program strategies to address the issue of street children, beggars, and homeless individuals.